Investigational drugs for recurrent or primary advanced metastatic cervical cancer: what is in the clinical development pipeline? - Vergote, Ignace; Ray-Coquard, Isabelle; Lorusso, Domenica; Oaknin, Ana; Cibula, David; Van Gorp, Toon (Expert opinion on investigational drugs, 2023)
INTRODUCTION: Recurrent or primary advanced metastatic cervical cancer (R/M CC) has a poor prognosis with a 5-year-survival rate of 16.5%, demanding novel and improved therapies for the treatment of these patients. The first-line standard of care for R/M CC now benefits from the addition of the immune checkpoint inhibitor, pembrolizumab, to platinum-based chemotherapy with paclitaxel and bevacizumab. Additionally, new options for second-line treatment have become available in recent years. AREAS COVERED: Here, we review current investigational drugs and discuss their relative targets, efficacies, and potential within the R/M CC treatment landscape. This review will focus on recently published data and key ongoing clinical trials in patients with R/M CC, covering multiple modes of action, including immunotherapies, antibody-drug conjugates, and tyrosine kinase inhibitors. We searched clinicaltrials.gov for ongoing trials and pubmed.ncbi.nih.gov for recently published trial data, as well as recent years' proceedings from the annual conferences of the American Society of Clinical Oncology (ASCO), European Society for Medical Oncology (ESMO), European Society of Gynaecological Oncology (ESGO), and the International Gynecologic Cancer Society (IGCS). EXPERT OPINION: Therapeutics currently attracting attention include novel immune checkpoint inhibitors, therapeutic vaccinations, antibody-drug conjugates, such as tisotumab vedotin, tyrosine kinase inhibitors targeting HER2, and multitarget synergistic combinations.
Keywords: tyrosine kinase inhibitor; Recurrent cervical cancer; testované léky; Female; combination therapy; ženské pohlaví; advanced metastatic cervical cancer; Drugs, Investigational; Immunotherapy; lidé; nádory děložního čípku; Paclitaxel; imunokonjugáty; imunoterapie; paclitaxel; investigational drugs; Uterine Cervical Neoplasms; immunotherapy; Immunoconjugates; antibody–drug conjugate; Humans